Pengaruh Gaya Kepemimpinan Situasional, Motivasi dan Pelatihan pada Kinerja Karyawan di Koperasi Pasar Srinadi Klungkung - Noviani, Ni Luh Komang Sri; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2018)
The purpose of this study was to obtain empirical evidence of the influence of situational leadership style, motivation and training on employee performance in the Srinadi Klungkung Cooperative Market. This study was conducted on all 350 employees and spread across nine Koppas Srinadi Klungkung business units. The number of samples taken was 78 employees, with probability sampling method, proportional random sampling technique. Data collection was carried out through surveys and questionnaires. The analysis technique used is multiple linear regression. Based on the results of the analysis and testing of hypotheses situational leadership style has a positive effect on employee performance, motivation has a positive effect on employee performance and training has a positive effect on employee performance. The positive influence of the variable situational leadership style, motivation and training on employee performance, has proven the theory used is the organizational behavior theory. Keywords : Situational leadership style, motivation, training, employee performance